Gamification for human factors integration : social, education, and psychological issues - Bishop, Jonathan, 1979- (Hershey, PA : Information Science Reference, 2014)
'This book presents information and best practices for promoting positive behavior online through gamification applications in social, educational, and psychological contexts'--
Includes bibliographical references (pages 290-325) and index.
Keywords: Internet -- Social aspects; Internet -- psychology; Interpersonal relations